2013
DOI: 10.4103/1947-2714.120795
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of acute kidney injury following snake bite envenomation

Abstract: Background:Snake bite envenomation is a major public health concern in developing countries. Acute kidney injury (AKI) is as important cause of mortality in patients with vasculotoxic snake bite.Aims:This study was to evaluate the clinical profile of snake bite patients and to determine the predictors of developing AKI following snake bite.Materials and Methods:Two hundred and eighty-one patients with snake envenomation were included. Eighty-seven patients developed AKI (Group A) and 194 (Group B) did not. His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…In addition, patients bitten by Viperidae who presented with capillary leakage, rhabdomyolysis, and hyponatremia were at increased risk for the development of sAKI during hospitalization. Previous studies reported similar factors associated with the sAKI, including receipt of antivenom >2 h after snakebite, cellulitis, hypotension, and rhabdomyolysis [9, 10, 13]. A previous case series from Taiwan showed that early specific antivenom treatment within 3 to 6 h after snake envenoming could restore coagulation abnormalities in 1 to 2 days and was effective in reducing the severity of renal damage [28].…”
Section: Discussionmentioning
confidence: 84%
“…In addition, patients bitten by Viperidae who presented with capillary leakage, rhabdomyolysis, and hyponatremia were at increased risk for the development of sAKI during hospitalization. Previous studies reported similar factors associated with the sAKI, including receipt of antivenom >2 h after snakebite, cellulitis, hypotension, and rhabdomyolysis [9, 10, 13]. A previous case series from Taiwan showed that early specific antivenom treatment within 3 to 6 h after snake envenoming could restore coagulation abnormalities in 1 to 2 days and was effective in reducing the severity of renal damage [28].…”
Section: Discussionmentioning
confidence: 84%
“…[ 4 ] They are neurotoxic Elapidae , including common Cobra ( Naja naja ), King Cobra ( Ophiophagus hannah ), and Krait ( Bungarus caeruleus , Bungarus fasciatus ); and vasculotoxic Viperidae , Russell's viper ( Daboia russelii ), and saw-scaled viper ( Echis carinatus ). [ 3 ] Acute renal failure is an important complication of Russell's viper and saw-scaled viper species of snakes in India. [ 7 ] Up to 70% of the protein content of viper venom is phospholipase A 2 , present in the form of at least seven isoenzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular hemolysis due to phospholipase A2 is a significant factor in the pathogenesis of snake bite-induced AKI. [ 3 ] The most common coagulopathy in snake bite is venom-induced consumption coagulopathy (VICC) which results from activation of the coagulation pathway by snake toxins. [ 16 ] In a proportion of patients with VICC, a clinical syndrome consistent with thrombotic microangiopathy has been reported, and it is characterized by acute renal failure, thrombocytopenia, and microangiopathic hemolytic anemia.…”
Section: Discussionmentioning
confidence: 99%
“…In India, patient-related factors such as child age, previous health condition and time elapsed until medical assistance can act as risk factors for severity, sequelae and death [ 22 26 ]. In the same country, patients admitted with symptoms of neurotoxicity and vomiting [ 22 , 24 ], coagulopathy and leukocytosis [ 23 ], hypertension, albuminuria, changes in bleeding and prothrombin time [ 25 ] were more likely to develop severe outcomes. The delay in antivenom administration was also a risk factor for severity in Nigeria [ 27 ].…”
Section: Introductionmentioning
confidence: 99%